Pengarahan tentang Pentingnya Pendidikan Usia Dini di Kampung Bulak, Kecamatan Pondok Gede, Bekasi - Nurhayadi, Yadi; Agasi, Agi Aditiya (Faculty of Economics and Business, University of Muhammadiyah Prof. DR. HAMKA, 2018)
Adult intelligence capabilities, associated with brain tissue development have reached 50 percent when he was 4 years old. The rapid development of brain tissue occurs when the child is 8 years old and reaches its peak when he is 18 years old. After that, although the improvement of nutrition will not affect cognitive development. This means that developments occurring in the first 4 years are as great as the development that occurred over the next 14 years. The first 4-year period is a critical period for children because it is very influential on the development of the next period until adulthood, while the golden period only comes once. Optimization of early childhood education, ie education of children at the age of 4 years first becomes very important. In fact the importance of early education is still not understood by some people. The direction and guidance of the importance of early education is required. This community service program provides direction and guidance on the importance of early childhood education to communities in kampung Bulak, Pondok Gede - Bekasi. This activity is also equipped with productive philanthropy in the form of procurement of library facilities for early childhood.